EARLY EDUCATION OF ACUTE KIDNEY INJURY AND PRE-RENAL PROBLEMS IN ANAPHYLACTIC SHOCK PATIENTS (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
Acute kidney injury (AKI) may manifest in patients experiencing anaphylactic shock. Arterial hypotension significantly contributes to the pre-renal etiology of AKI. The condition of anaphylactic shock is a life-threatening situation that requires immediate intervention. The decrease in perfusion to the renal organs in patients with acute anaphylactic shock can lead to the development of acute kidney injury (AKI). This is characterized by an increase in the Urine (U) and Creatinine (Cr) ratio (>20:1) and is reversible if promptly managed through fluid resuscitation, which results in a decrease in serum creatinine levels. Anaphylactic shock can lead to the occurrence of pre-renal acute kidney injury (AKI), which can be reversible if promptly addressed.